Pengolahan Briket Bio-Arang Berbahan Dasar Kotoran Kambing dan Cangkang Kemiri di Desa Galung Lombok Kecamatan Tinambung, Polewali Mandar - Sulmiyati Sulmiyati; Nur Saidah Said (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
The problems faced by farmers in Galung Lombok Village is knowledge in the in the processing of goat livestock manure and waste of hazelnut shell. The solution that can be offered is waste treatment into bio-charcoal briquettes. The community engagement is to introduce community or partners of Community Partnership Program (CPP) in processing livestock manure and agricultural waste into charcoal briquettes as an alternative solution to the problems faced by society and become an alternative business potential that can be developed by farmers. The methods applied in overcoming these problems are through interactive counseling, training with the demonstration of bio-charcoal briquette processing, guidance and mentoring into ready to market products. The results of the dedication activities were held on 13-14 May 2017 at the meeting hall of Siamasei Farmer Group of Galung Lombok Village, Tinambung, Polewali Mandar. This activity is carried out by conducting participatory counseling coupled with demonstrations of processed briquettes from goat manure and hazelnut shell, packaging, and testing of briquette quality. The conclusion that goat livestock manure can be processed into bio-charcoal briquettes through seven stages: drying of raw materials, refining, reducing and filtering, adhesive mixing, printing, drying and packaging. The quality of briquettes produced,the moisture content of 5.58%, ash content of 23.93%, volatile matter of 35.16%, fixed carbon of 35.33%, and calories 4,563 cal/gr.